Dosimetric comparison of Acuros XB with collapsed cone convolution/superposition and anisotropic analytic algorithm for stereotactic ablative radiotherapy of thoracic spinal metastases. (8th July 2015) - Zhen, Heming; Hrycushko, Brian; Lee, Huichen; Timmerman, Robert; Pompoš, Arnold; Stojadinovic, Strahinja; Foster, Ryan; Jiang, Steve B.; Solberg, Timothy; Gu, Xuejun
Abstract : The aim of this study is to compare the recent Eclipse Acuros XB (AXB) dose calculation engine with the Pinnacle collapsed cone convolution/superposition (CCC) dose calculation algorithm and the Eclipse anisotropic analytic algorithm (AAA) for stereotactic ablative radiotherapy (SAbR) treatment planning of thoracic spinal (T‐spine) metastases using IMRT and VMAT delivery techniques. The three commissioned dose engines (CCC, AAA, and AXB) were validated with ion chamber and EBT2 film measurements utilizing a heterogeneous slab‐geometry water phantom and an anthropomorphic phantom. Step‐and‐shoot IMRT and VMAT treatment plans were developed and optimized for eight patients in Pinnacle, following our institutional SAbR protocol for spinal metastases. The CCC algorithm, with heterogeneity corrections, was used for dose calculations. These plans were then exported to Eclipse and recalculated using the AAA and AXB dose calculation algorithms. Various dosimetric parameters calculated with CCC and AAA were compared to that of the AXB calculations. In regions receiving above 50% of prescription dose, the calculated CCC mean dose is 3.1%–4.1% higher than that of AXB calculations for IMRT plans and 2.8%–3.5% higher for VMAT plans, while the calculated AAA mean dose is 1.5%–2.4% lower for IMRT and 1.2%–1.6% lower for VMAT. Statistically significant differences ( p < 0.05 ) were observed for most GTV and PTV indices between the CCC and AXB calculations for IMRT and VMAT, while differences between the AAA and AXB calculations were not statistically significant. For T‐spine SAbR treatment planning, the CCC calculations give a statistically significant overestimation of target dose compared to AXB. AAA underestimates target dose with no statistical significance compared to AXB. Further study is needed to determine the clinical impact of these findings. PACS number: 87.55.D‐, 87.53.Ly